LEARNING INNOVATION THROUGH EDUCATIONAL GAMES IN INCREASING ELEMENTARY SCHOOL CHILDREN'S INTEREST IN LEARNING - Baso Intang Sappaile (Indonesian Journal of Education (INJOE), 2025)
Technological advancements and changes in children's learning patterns necessitate innovative teaching methods that can enhance elementary school students' interest in learning. One form of innovation widely used is educational games, whether in digital form, board games, role-playing, or gamification. This research is a literature review aimed at analyzing the role of educational games in increasing elementary school children's interest in learning, as well as identifying supporting factors and challenges in their implementation. The research method used is a literature study, reviewing various relevant sources such as journals, books, and research reports. The study results indicate that educational games can increase intrinsic and extrinsic motivation, foster curiosity, and create a more enjoyable learning environment. Additionally, games also encourage active student engagement and strengthen social interaction within the classroom. Factors supporting the successful implementation of educational games include teacher support, creativity, the availability of infrastructure, and collaboration with parents. However, the challenges faced include time constraints, teacher readiness, media costs, and alignment with learning outcomes. Therefore, a sustainability strategy needs to be prepared so that educational games can be effectively integrated into learning. This research suggests the need for further study regarding the effectiveness of digital educational games and their integration into the Merdeka Belajar curriculum.